Transition from preschool to school: Children's pattern of change in morning cortisol concentrations. (June 2022) - Leblond, Maggy; Parent, Sophie; Castellanos-Ryan, Natalie; Lupien, Sonia J.; Fraser, William D.; Séguin, Jean R.
Abstract: Many studies show a general increase in stress hormones at the exposure to school entry, but inconsistencies among them due to small samples with varying methodologies and very few time-points, preclude robust conclusions. The current study aimed to describe the pattern of morning cortisol concentration in children across the transition from preschool to school by examining whether we could identify a response to the school entry, but also an anticipatory stress response (pre-entry) and a stress adaptation response (post-entry). We further tested the robustness of this pattern across several characteristics. Participants were 384 children recruited from two cohorts of the 3D pregnancy study, and followed across their transition from preschool to kindergarten. Children's morning salivary cortisol samples were collected over five time-points: twice before school entry, once at school entry and twice after school entry (one sample per time-point). Although no anticipatory stress response was observed two weeks before school entry, latent growth curve models showed that most children's morning cortisol concentrations increased during the first two weeks of school, and was not associated with any sociodemographic characteristics, supporting the hypothesis that school entry is a normative environmental stressor. In contrast, two months after school entry, some children showed stress adaptation whereas others showed a prolonged stress response to school entry. This between-children variance could not be explained by any specific sociodemographic characteristic. This study showed that the morning stress response rises at school entry and is sustained for at least two weeks in most children. However, the observed variability in the stress adaptation response remains to be elucidated and linked to functional correlates. Highlights: Morning cortisol concentrations were measured 5 times across the school transition. Children showed no anticipatory stress response before school entry. Children showed a stress response (increase) during the first two weeks of school. Children showed varying rates of stress adaptation two months after school entry. Supports the idea that school entry is a normative environmental stressor.